Changes in fear-associated learning task brain activation over the COVID-19 pandemic period: a preliminary longitudinal analysis - Popovich, Claire; Grau, Aaron S.; Shih, Chia-Hao; Chidiac, Neejad T.; Zhou, Adrian; Wang, Xin; Xie, Hong (Frontiers in Psychiatry, 2023)
Background. The COVID-19 pandemic has had profound impacts on people worldwide. Previous studies have shown that fear learning, extinction, recall, and contextual information processing involve activation in emotion and sensory brain systems, which can be modified. However, it remains unclear whether brain functions associated with these processes are altered over the pandemic period. Methods. We compared pre-and peri-pandemic brain activation during a Fear Associated Learning Task (FALT) using previously collected data. The participants were divided into two groups: the Pandemic group, who completed a baseline FALT before the pandemic and repeated the task during the pandemic, and the non-Pandemic group, who completed both sessions before the pandemic began. Results. Compared to the non-Pandemic group, the Pandemic group exhibited significant decreases in brain activation from baseline to follow-up assessments, including activation in the brainstem during early fear learning, the posterior thalamus/hippocampus during late extinction, and the occipital pole during late recall phases for contextual processing. Furthermore, activations associated with retrieving safety cues were reduced in the posterior cingulate, premotor, and calcarine cortices during the early recall phase, and activation associated with retrieving dangerous cues decreased in the occipital pole during the late recall phase. Additionally, correlations between decreased activation and elevated posttraumatic stress symptoms were observed. Conclusions. These findings suggest that activation associated with processing low arousal contextual information, safety cues, and extinguished fear cues decreased during the pandemic. These changes in brain activation may contribute to the increase in mental health disturbances observed during this time.